2022
DOI: 10.3847/1538-4357/ac9eb6
|View full text |Cite
|
Sign up to set email alerts
|

Quasiperiodic Erupters: A Stellar Mass-transfer Model for the Radiation

Abstract: Quasiperiodic erupters are a remarkable class of objects exhibiting very-large-amplitude quasiperiodic X-ray flares. Although numerous dynamical models have been proposed to explain them, relatively little attention has been given to using the properties of their radiation to constrain their dynamics. Here we show that the observed luminosity, spectrum, repetition period, duty cycle, and fluctuations in the latter two quantities point toward a model in which a main-sequence star on a moderately eccentric orbit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Several authors have invoked stable mass transfer from a compact star or WD onto a low-mass SMBH (e.g., King 2020;Zhao et al 2022;King 2022). Mass transfer from an MS star has been recently proposed in Krolik & Linial (2022), where shocks from self-intersecting streams of material have been considered as the source of radiation. MS stars have also been considered by Metzger et al (2022), who suggested that QPE flares arise from interaction between two counterrotating MS stars on circular orbits near the tidal radius, shedding an excess of mass at each conjunction of the two stars.…”
Section: Quasiperiodic Eruptions From Unstable Mass Transfer From a M...mentioning
confidence: 99%
See 3 more Smart Citations
“…Several authors have invoked stable mass transfer from a compact star or WD onto a low-mass SMBH (e.g., King 2020;Zhao et al 2022;King 2022). Mass transfer from an MS star has been recently proposed in Krolik & Linial (2022), where shocks from self-intersecting streams of material have been considered as the source of radiation. MS stars have also been considered by Metzger et al (2022), who suggested that QPE flares arise from interaction between two counterrotating MS stars on circular orbits near the tidal radius, shedding an excess of mass at each conjunction of the two stars.…”
Section: Quasiperiodic Eruptions From Unstable Mass Transfer From a M...mentioning
confidence: 99%
“…The resulting emission would be strongly modulated over the orbital period P, as long as the dissipation mechanism is capable of rapidly dissipating the orbital energy of the mass transfer stream, and as long as the heated material can readily cool to allow for large variability in the emitted flux (e.g., Krolik & Linial 2022). One natural dissipation mechanism capable of producing the high amplitude, short duty cycle, and observed temperature of the QPE flares is due to shocks occurring when streams of mass transfer self-intersect near the ISCO of the SMBH, as discussed in Krolik & Linial (2022). On the other hand, the long viscous timescale of a standard accretion disk (τ visc ?…”
Section: Orbital Period and Qpe Recurrence Timementioning
confidence: 99%
See 2 more Smart Citations
“…The primary challenges of this phenomenon are how to construct a physical scenario to produce such short periodic eruptions (several to a dozen of hours). A number of models have been proposed, which can be roughly divided into two categories: while the first one suggests that the periodic outbursts in QPEs originate from the periodic orbital motion of a star captured by a black hole (King 2020(King , 2022Ingram et al 2021;Suková et al 2021;Xian et al 2021;Chen et al 2023;Krolik & Linial 2022;Lu & Quataert 2022;Linial & Sari 2023;Metzger et al 2022;Wang et al 2022b;Franchini et al 2023;Linial & Metzger 2023;Tagawa & Haiman 2023), another one ascribes the periodic behavior to the instability of inner accretion disk dominated by radiation pressure (Sniegowska et al 2020;Pan et al 2021Pan et al , 2022Raj & Nixon 2021;Kaur et al 2023;Śniegowska 2023). Notably, only the model of Pan et al (2022) is able to fit both the light curves and the phase-resolved X-ray spectra simultaneously during outbursts in GSN 069.…”
Section: Introductionmentioning
confidence: 99%